Development and characterization of finger-jointed laminated bamboo timber for furniture construction - Anokye, Rogerson; Bakar, Edi Suhaimi; Ratnasingam, Jegatheswaran; Ashaari, Zaidon; Awang, Khairul (Indonesian Wood Research Society, 2014)
Laminated bamboo timber (LBT) are found to have a high tensile strength and modulus, good resistance to fatigue loadings, primarily due to its fiber properties. However, it is reported that LBT production is quit inefficient and are not well accepted due to the presence of nodes that disfigures the surface appearance of the board. Accordingly, V-grooving method was developed to counteract these inefficiencies but still with other problems requiring the lengthening of the short clear bamboo strips with finger-joints. The mechanical properties of the finger-jointed clear Gigantochloa scortechinii bamboo species was therefore evaluated in static bending test using the bamboo strips selected for strip with finger joints specimens, with node and without node. Based on the distance between the joints, the best finger-jointed LBT strength was found to increase from 5 to 10cm and 5 to 15cm by 30.26% and 49.12% respectively. In the case is glue spread rate, there was an increase in MOR of 61.49% and 41.79% with phenol formaldehyde over the use of polyvinyl acetate at 250g/m2 and 200g/m2 respectively. The structural performance of finger-jointed LBT also showed a 31.87% higher in MOR than its counterpart with nodes.